Eksistensi Aspek Teknologi dalam Pembuatan Akta Autentik Secara Elektronik pada Pengaturan Jabatan Notaris di Era Industri 5.0 - Ade Irawan; M. Ryan Bakry; Frengki Hardian (Publikasi Indonesia, 2022)
This study describes the concept of the existence of technological aspects and the form of regulation of the office of notary in the technology-based industrial era 5.0 in making authentic deeds electronically (cyber notary), with a doctrinal legal research method using a statutory approach and a conceptual approach made from primary, secondary, tertiary law with qualitative analysis. The results of this study state that the existence of technological aspects in making notarial authentic deeds in the industrial era 5.0 conceptually needs to be made an integrated notary system in the form of a digital application (platform) integrated with various institutions/ministries, so that the reading of deeds, fingerprints and signatures of various parties can be done digitally and real time validation of documents that are the basis for making the deed until the form of notarial deed is paper less (without paper media). Thus, the form of regulation of the office of notary in the era of technology-based industry 5.0 in making authentic deeds must be able to answer and respond to various developments and changes in social dynamics in society. To meet legal needs, the legislators need to realize progressive law.